Managing factors affecting the professional attachment of physical education school teachers in Vietnam - Hao, Tran Anh; Dien, Tran Van (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
In Vietnam, from August 2023 to April 2024, according to the Ministry of Education and Training, 7,215 teachers will leave or change jobs. This highlights the importance of addressing factors affecting the professional commitment of physical education teachers, a key issue for the Party, the State and society. This study examines factors affecting the professional commitment of physical education teachers in both positive and negative ways. A survey of 3,000 teachers found that 64.4% were female and 49.1% were in their 40s. Most had 5-10 years (40.75%) or 10-20 years (35.25%) of experience. The survey also included professional team leaders (2.5%) and school board members (1%). The study identified six factors affecting the professional commitment of physical education teachers: (1) income, (2) working environment, (3) management relationships, (4) training and promotion, (5) self-efficacy, and (6) relationships with colleagues. Based on these findings, the study proposes a model and solutions to improve professional commitment, ensuring the sustainable development of education in Vietnam.